2020
DOI: 10.4236/acs.2020.102010
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Local Carbon Fluxes Variations and Their Relationship to Climate Conditions in a Sub-Humid Savannah-Ecosystem during 2008-2015: Case of Lamto in Cote d’Ivoire

Abstract: The temporal variations of the Gross Primary Productivity (GPP), the Total Ecosystem Respiration (TER) and the Net Ecosystem Exchange (NEE), and their responses to meteorological conditions (e.g. temperature, radiative flux and precipitation) at Lamto, in wet savannah region across Côte d'Ivoire are analyzed using GFED-CASA and daily meteorological data recorded over the 2008-2015 period. The study shows the links between these carbon fluxes and climate variability at Lamto that is subject to high anthropogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 67 publications
1
12
0
Order By: Relevance
“…It was observed that this oceanic cluster is much more frequent during the wet seasons (Figure 11), coinciding with the West African Monsoon (WAM) period, which could have an impact on concentrations. Indeed, the WAM period is associated with less significant variability in temperature and radiative flux, which are the main explicative variables of the seasonal dynamics of carbon fluxes in the region [36]. In addition, contributions from retro-plumes of exclusively Atlantic origins are ≈35% over the study period, which shows that the transport of air masses associated with the WAM strongly influences…”
Section: Impacts Of Transport On the Concentrations Of Co Co2 And Ch4mentioning
confidence: 87%
See 1 more Smart Citation
“…It was observed that this oceanic cluster is much more frequent during the wet seasons (Figure 11), coinciding with the West African Monsoon (WAM) period, which could have an impact on concentrations. Indeed, the WAM period is associated with less significant variability in temperature and radiative flux, which are the main explicative variables of the seasonal dynamics of carbon fluxes in the region [36]. In addition, contributions from retro-plumes of exclusively Atlantic origins are ≈35% over the study period, which shows that the transport of air masses associated with the WAM strongly influences…”
Section: Impacts Of Transport On the Concentrations Of Co Co2 And Ch4mentioning
confidence: 87%
“…On the other hand, cluster C shows peaks (February-March and October) which are observed during changes in rainfall regimes at Lamto (i.e., from dry season to wet season and wet season to dry season). Cluster D is ubiquitous throughout the year with significant peaks observed in May and October, corresponding to the months when the station records significant peaks of precipitation ( Figure 2) [36]. Figure 11 shows the seasonal frequency for each of the four clusters.…”
Section: − Cluster Dmentioning
confidence: 99%
“…It is owned and operated as a nature reserve by Nangui Abrogoua University, where the senior author holds a faculty position; thus, external permission to conduct research on this site was not required. The average annual rainfall in the Lamto Reserve is about 1,200 mm and the average temperature is 28.6°C (Tiemoko et al, 2020). The climate is sub‐equatorial with four seasons based on monthly rain: a long rainy season from mid‐March to July, a short dry season in August, a short rainy season from September to mid‐November and a long dry season from mid‐November to mid‐March.…”
Section: Methodsmentioning
confidence: 99%
“…This method shows robust and specific performances to objectively determine one or more trend breaks in time-series when they occur. In addition, it has been used in many studies on climate variability in West Africa (Diawara et al, 2014;Ta et al, 2016;Tiemoko et al, 2020a).…”
Section: Methodsmentioning
confidence: 99%
“…This seasonality of the CO 2 cycle reflects the seasonality of the terrestrial vegetation fluxes and atmospheric transport. Also, the studies of Ago (2016) and Tiemoko et al(2020a) on West African ecosystems indicated that photosynthesis is dominant during the rainy season and respiration exceeds it during the dry season. Compared to ASK, IZO and CVO, the maximum concentration at LTO occurs about 4 months earlier, in January.…”
Section: Seasonal Cycles Of Co 2 Ch 4 and Comentioning
confidence: 99%